Trends and Implementation of School Branding Strategies to Increase Public Trust: Systematic Literature Review - Nabilah Khonsa; Rugaiyah Rugaiyah; Desi Rahmawati; Syafa’at Ariful Huda (Journal of Educational Sciences, 2026)
The phenomenon of declining public interest in a number of schools indicates that public trust has become a strategic issue in education management. This study aims to analyze how school branding strategies can increase public trust and identify the most influential branding components in building the reputation of educational institutions. The research method used is a Systematic Literature Review (SLR) with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, examining scientific publications published in 2020–2025 obtained through Publish or Perish from the Scopus and Google Scholar databases. The results show that school branding is not only related to promotion or visual identity, but is a sustainable managerial strategy that encompasses the quality of educational services, information transparency, academic reputation, and the use of digital media. The study concludes that school branding strategies play a crucial role in building social trust between schools and the community, as well as being a strategic factor in supporting the reputation, sustainability, and competitiveness of educational institutions amidst the dynamics of change and increasing public demands.